PENGARUH MOTIVASI, KEPUASAN KERJA DAN PENEMPATAN PEGAWAI TERHADAP KINERJA PENYULUH LAPANGAN KELUARGA BERENCANA DI KABUPATEN KARANGASEM - I Gusti Agung Bagus Cakra (Journal of Applied Management Studies, 2021)
The success of the community empowerment program and family planning must be supported by the performance of the Family Planning Field Extension Officer, which is reflected in the performance targets, the level of achievement of the Family Planning Field Instructor's performance in Karangasem Regency is still below the target. This study aims to determine the effect of motivation, job satisfaction and employee placement on the performance of family planning field counselors. This research is a quantitative correlational type, using the exposed facto method, with a total sample of 54 selected by total sampling. The data were analyzed using Multiple Regression Analysis, T-test and F test. The results showed the tcount of X¹ (2.234), X² (2.318) and X³ (2.355)> t table = 1.675 and a significant value of 0.040 <5%, then the hypothesis which states that the three variables X partially affect Y can be accepted. The results of the F test obtained that the F count of 44.282, this value is greater than the F table, namely 3.99 or Fcount 12.521> Ftable 12.786 with a probability of 0.008, indicating that the three X variables simultaneously affect employee performance. It is advisable for agencies to pay attention to the division of labor in accordance with the ability of employees based on the level of education the employee has. In addition, it can also be done by providing opportunities for employees to take part in special education and skills.